Baseline preseason ImPACT® testing in Mandarin with adolescent student-athletes in the United States. Issue 3 (3rd July 2022) - Iverson, Grant L.; Karr, Justin E.; Hong, Yue; Yang, Chi-Cheng; Maxwell, Bruce; Berkner, Paul D.
Abstract: Researchers have examined differences on ImPACT ® in baseline symptom reporting and neurocognitive performances based on the language of administration and racial/ethnic identity. This is the first study to examine differences between student-athletes tested in Mandarin versus English on ImPACT ® during preseason baseline assessments conducted in high schools in the United States. Participants included 252 adolescent student-athletes who completed ImPACT ® testing in the state of Maine in Mandarin and 252 participants who completed testing in English, matched on age, gender, and health and academic history. Participants were compared on neurocognitive composite scores and symptom ratings. Boys tested in Mandarin, but not girls, had modestly better neurocognitive performance on one of four composite scores (i.e., Visual Motor Speed, p < .001, d = .45). Although language groups did not differ in total symptom severity, boys tested in Mandarin endorsed multiple physical symptoms at higher rates than boys tested in English. These results suggest that the current ImPACT ® neurocognitive normative data are reasonably appropriate for use with adolescents evaluated in Mandarin. There were some differences in the reporting of physical symptoms, with greater rates of symptom endorsement by boys tested in Mandarin than boys tested in English; but overall symptom severity ratings were comparable between the language groups.